What is the optimal mode of mechanical support in transplanted patients with acute graft failure? - Urban, Marian; Szarszoi, Ondrej; Pirk, Jan; Netuka, Ivan (Interactive cardiovascular and thoracic surgery, 2013)
A best evidence topic in cardiac surgery was written according to a structured protocol. The question addressed was: is extracorporeal membrane oxygenation (ECMO) superior to dedicated ventricular assist device (VAD) in patients with acutely failing allograft following transplantation. Altogether, 162 papers were found using the reported search, of which 8 represented the best evidence to answer the clinical question. The authors, journal, date and country of publication, patient group studied, study type, relevant outcomes and results of these papers are tabulated. Two studies provide data only for ECMO-treated patients, in three, the authors describe their experiences with Levitronix CentriMag and three studies directly compare the outcomes of ECMO and VAD support. The survival ranges from 40 to 74% in patients rescued with ECMO compared with 33-60% in patients supported with dedicated VAD. We conclude that there is insufficient evidence to prefer ECMO over VAD and the optimal modality of mechanical circulatory support (MCS) following heart transplantation should be determined by the surgeon and institutional experience and dependent on the extent and severity of myocardial dysfunction and the presence or absence of associated respiratory insufficiency.
Keywords: Heart Transplantation; Extracorporeal Membrane Oxygenation; mimotělní membránová oxygenace; výsledek terapie; komorová dysfunkce; Hemodynamics; Heart-Assist Devices; hemodynamika; časové faktory; funkce levé komory srdeční; Time Factors; lidé; Survival Analysis; Treatment Outcome; funkce pravé komory srdeční; Respiratory Insufficiency; Risk Factors; Ventricular Function, Right; podpůrné srdeční systémy; Ventricular Dysfunction; medicína založená na důkazech; transplantace srdce; rizikové faktory; analýza přežití; Benchmarking; Evidence-Based Medicine; respirační insuficience; Ventricular Function, Left; benchmarking; Humans